1994
DOI: 10.1007/bf00609405
|View full text |Cite
|
Sign up to set email alerts
|

Heart rate threshold related to lactate turn point and steady-state exercise on a cycle ergometer

Abstract: The aim of this study was to investigate heart rate threshold (HRT) related exercise intensities by means of two endurance cycle ergometer tests using blood lactate concentration [La], pulmonary ventilation (VE), oxygen uptake (VO2), heart rate (HR) and electromyogram (EMG) activity of working muscle. Firstly, 16 healthy female students [age, 21.4 (SD 2.8) years; height, 167.1 (SD 5.1) cm; body mass 62.7 (SD 7.1) kg] performed an incremental exercise test (10 W each minute) on an electrically braked cycle ergo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

8
69
2
5

Year Published

2003
2003
2016
2016

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 75 publications
(84 citation statements)
references
References 34 publications
8
69
2
5
Order By: Relevance
“…Some studies (8,9) have used the graphic visual method for the estimate of the disproportionate increase in ventilatory and metabolic variables, during the incremental dynamic exercise, as a gold standard for the quantification of AT. Additionally, other investigators have identified AT by analysis of heart rate (HR) (3,(10)(11)(12)(13) and of its variability (14), as well as by surface electromyography analysis (15)(16)(17).…”
Section: Introductionmentioning
confidence: 99%
“…Some studies (8,9) have used the graphic visual method for the estimate of the disproportionate increase in ventilatory and metabolic variables, during the incremental dynamic exercise, as a gold standard for the quantification of AT. Additionally, other investigators have identified AT by analysis of heart rate (HR) (3,(10)(11)(12)(13) and of its variability (14), as well as by surface electromyography analysis (15)(16)(17).…”
Section: Introductionmentioning
confidence: 99%
“…Há estudos que tentam classificar a população quanto a sua capacidade aeróbia 19,20 outros equiparar protocolos 5 , porém a utilização de parâmetros diferentes torna difícil a comparação entre eles. Então, surge a necessidade de desenvolver metodologias que possam facilitar esse tipo de análise.…”
Section: Discussionunclassified
“…Esse parâmetro de capacidade aeróbia tem sido identificado por meio da concentração sangüínea de lactato 1,2 pela determinação de alterações nas trocas gasosas, chamado de limiar de anaerobiose ventilatório (LAV) 3,4 , pela resposta da freqüência cardíaca 3,5 e/ou pela eletromiografia de superfície 6 .…”
Section: Introductionunclassified
“…Conconi et al (1982) propuseram inicialmente um método não-invasivo que seria coincidente ao limiar anaeróbio e de fácil aplicação em teste de campo. Baseado na validade do limiar anaeróbio com a MFEL (HECK et al, 1985;SIMOES et al, 1999), alguns trabalhos utilizaram o limiar anaeróbio como estimativa da MFEL na comparação com o PDFC visual (HOFMANN; LEITNER; GAISL, 1992;HOFMANN et al, 1994;BUNC et al, 1995;BOURGOIS et al, 2004). Em nosso estudo não foi observado diferença entre as velocidades do PDFC visual e MFEL, além de uma correlação significante (r = 0,75).…”
Section: Análise Estatísticaunclassified
“…Em nosso estudo não foi observado diferença entre as velocidades do PDFC visual e MFEL, além de uma correlação significante (r = 0,75). Corroborando com os nossos resultados, alguns estudos verificaram valores semelhantes em variáveis metabólicas e cardiovasculares 6 relacionados ao PDFC visual e limiar anaeróbio em ciclo ergômetro (HOFMANN; LEITNER; GAISL, 1992;HOFMANN et al, 1994;BUNC et al, 1995;BOURGOIS et al, 2004 Bourgois et al (2004) onde somente um (n = 10) e quatro (n =11) sujeitos demonstraram equilíbrio na concentração de lactato sanguíneo, respectivamente. Além disso, o tempo médio dos estudos acima foi similar ao nosso (17,5 ± 11,1min e 23,8 ± 8,8min respectivamente).…”
Section: Análise Estatísticaunclassified